PENGARUH PERILAKU KONSUMEN TERHADAP KEPUASAN PENGGUNA PROGRAM TIKTOK SHOP PADA WANITA PEKERJA - Rizky Elliandra Shasqia Anindhita (JURNAL ISLAMIKA, 2023)
Consumer behavior is a behavior shown from consumers when planning a purchase and after using a product/service for satisfying the needs and desires of consumers. Consumer satisfaction is a feeling of consumers after making a purchase and using a product/service. If the consumer want to repurchase, that means the consumer is satisfied with the product they purchased before. Consumers who are satisfied with the experience of online shopping will have higher expectations for the future, and this will lead to loyalty. This study aims to determine the effect of consumer behavior on consumer satisfication in the TikTok Shop program for female workers. The sample in this study is 96 people. Data collection uses a consumer behavior scale with 13 items, and a consumer satisfaction scale with 21 items. Data analysis using simple linear regression test. The results of data analysis show the value of F = 70.833 with a sig value of 0.000 (P < 0.05), which means there is an influence between consumer behavior on consumer satisfaction in the TikTok Shop program for female workers. The results also show that the value of R Square is 0.430, which means that consumer behavior has an influence of 43% on consumer satisfaction, while 57% is influenced by other variables not examined in this study. Keywords: Consumer behavior, Consumer satisfication, TikTok shop, Female worker